2015
DOI: 10.1080/02687038.2015.1016888
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perspectives on community aphasia groups: a narrative literature review in the context of psychological well-being

Abstract: Background: Community aphasia groups (CAGs) for people living with chronic aphasia are known to be efficacious for improving various aspects of communication and psychological functioning based on empirical quantitative evidence. However, the specific mechanisms and processes involved are not well understood and only a small number of groups exist. Further, there is a paucity of evidence on this topic from consumers, potentially limiting the development and uptake of these services. In order to proliferate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 69 publications
1
18
0
1
Order By: Relevance
“…Other factors that fueled the paradigm shift included recognition of the need for interventions that improved quality of life and overall well-being for people with aphasia (Brown, Worrall, Davidson, & Howe, 2012;Hilari, Needle, & Harrison, 2012;Holland & Nelson, 2013;LeDorze & Brassard, 1995;Parr, Byng, Gilpin, & Ireland, 1997;Sarno, 1991Sarno, , 1993Ross & Wertz, 2003) and reduced the negative impact of social isolation that often resulted from aphasia (Attard, Lanyon, Togher, & Rose, 2015;Davidson, Howe, Worrall, Hickson, & Togher, 2008;Elman, 2007b;Elman & Bernstein-Ellis, 1999b;Hilari & Northcott, 2006;Rotherham, Howe, & Tillard, 2015;Ryff, 1989;Ryff & Singer, 2000;Ryff, Singer, & Love, 2004;Vickers, 2010;Worrall et al, 2011). There was also increasing recognition that people with aphasia could receive benefit from opportunities for authentic conversation and development of social relationships that were typical in dyads and groups (Elman, 2007a(Elman, , 2007bEwing, 2007;Simmons-Mackie & Elman, 2011;Simmons-Mackie et al, 2014;Yalom, 2005).…”
Section: Additional Factors That Supported the Creation Of Aphasia Cementioning
confidence: 98%
“…Other factors that fueled the paradigm shift included recognition of the need for interventions that improved quality of life and overall well-being for people with aphasia (Brown, Worrall, Davidson, & Howe, 2012;Hilari, Needle, & Harrison, 2012;Holland & Nelson, 2013;LeDorze & Brassard, 1995;Parr, Byng, Gilpin, & Ireland, 1997;Sarno, 1991Sarno, , 1993Ross & Wertz, 2003) and reduced the negative impact of social isolation that often resulted from aphasia (Attard, Lanyon, Togher, & Rose, 2015;Davidson, Howe, Worrall, Hickson, & Togher, 2008;Elman, 2007b;Elman & Bernstein-Ellis, 1999b;Hilari & Northcott, 2006;Rotherham, Howe, & Tillard, 2015;Ryff, 1989;Ryff & Singer, 2000;Ryff, Singer, & Love, 2004;Vickers, 2010;Worrall et al, 2011). There was also increasing recognition that people with aphasia could receive benefit from opportunities for authentic conversation and development of social relationships that were typical in dyads and groups (Elman, 2007a(Elman, , 2007bEwing, 2007;Simmons-Mackie & Elman, 2011;Simmons-Mackie et al, 2014;Yalom, 2005).…”
Section: Additional Factors That Supported the Creation Of Aphasia Cementioning
confidence: 98%
“…There is strong evidence that community‐based aphasia groups hold value for people with aphasia (Elman , Graham and Avent , Attard et al . , Rotherham et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that community aphasia groups fulfil critical support, communication and education needs (Attard et al . ), and offer opportunities for relationship formation (Rotherham et al . , Shadden ).…”
Section: Introductionmentioning
confidence: 99%
“…Like Cartwright and Elliot's (2009) participants, ANT and RBI both reported that they appreciated the opportunity to communicate with others on an equal level and were especially motivated when they could help other group members. We believe that the exchange of experiences is an especially important feature of the communicative group setting for people with PPA just as it is in post-stroke aphasia (Attard, Lanyon, Togher, & Rose, 2015;Masoud, Arnold, Schilikowski, Simon, & Simon, 2009).…”
Section: Modifications To the Ciat Protocolmentioning
confidence: 99%